(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article analyzes the theoretical approaches of sociological scientific schools to social prevention of crime. Each school - functionalism, conflictology, interactionism, cultural-cognitive and poststructuralism - interprets crime based on its own methodology. The author substantiates the need to integrate various theories as a comprehensive approach.